Methodology for the development of maintenance management systems based on the NTE- INEN-EN-15341 standard in manufacturing MSMEs in the province of Imbabura (Innovation & Development in Engineering and Applied Science, 2025)
Maintenance management in companies, whether large, small or medium-sized, is important since it allows adequate work of the machinery and operation of the processes, the research focuses on the design of a methodology for maintenance management, in manufacturing MSMEs in the province of Imbabura, which was divided into phases. Phase I. The population and sample selection were identified by applying statistical formulas and the type of economic activity they generate, obtaining a sample of 340 manufacturing MSMEs, In phase II, information was collected by applying the MES survey (Maintenance Effectiveness Survey), which consists of a set of questions related to the administration and management of maintenance that seeks to identify the level of maintenance carried out in manufacturing MSMEs in the region. province of Imbabura, as well as the processes that are carried out to fulfill the declared economic activity, where the strategic, operational and support processes were identified, it is necessary to emphasize that as they are manufacturing companies and their focus is production of clothing, food, leather goods, among others, have specialized machinery that must provide adequate operating and operational conditions. In phase II, once the information is obtained, the methodology for maintenance management in MSMEs, manufacturing companies in the province of Imbabura, is proposed, considering the situational diagnosis, design, implementation and verification.
Keywords: MSMEs; Maintenance Management; MES Survey; Maintenance Effectiveness Survey